Human Rights and Multilateral Diplomacy. A perspective of the Dicastery for Promoting Integral Human Development on the Right to Life - Christine Jeangey (Chrześcijaństwo-Świat-Polityka)
The article describes the contribution and activities of the Pontifical Department for the Promotion of integral human development. The Holy See as a subject of international law participates in multilateral negotiations, especially in international organizations such as the United Nations, making a concrete effort to promote the right to life, which today is often denied or even combated as a limitation of other (false) rights recognized as new human rights.